2018
DOI: 10.5650/jos.ess18038
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Texture of Cosmetic Sponges and Their Friction Behavior under Accelerated Movement

Abstract: We evaluated the friction properties of five cosmetic sponges on artificial skin using sinusoidal motion-friction evaluation system. No significant difference was observed in the pleasant score of the five sponges when these sponges were rubbed on the skin surface. The sponges were classified into three groups based on their tactile feel. Their characteristic tactile textures were moist-soft-slippery, moist-dry-rough, and moist feels. The slippery feel was found to depend on the thickness of the sponge's cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…One of the major focuses in skin tribology was the relation between tribological properties and skin perception, tactile and haptics, particularly the finger [471,472]. Both the skin and the perceived objects were involved in the contact and therefore were important considerations, including surface texture [473,474], softness [475], and chemistry [476], etc. Perception was correlated with tribological properties such as friction, vibration, stickiness, contact mechanics [477], and different environments [478,479], and different subjects including age, gender, etc [480,481].…”
Section: Skin Tribologymentioning
confidence: 99%
“…One of the major focuses in skin tribology was the relation between tribological properties and skin perception, tactile and haptics, particularly the finger [471,472]. Both the skin and the perceived objects were involved in the contact and therefore were important considerations, including surface texture [473,474], softness [475], and chemistry [476], etc. Perception was correlated with tribological properties such as friction, vibration, stickiness, contact mechanics [477], and different environments [478,479], and different subjects including age, gender, etc [480,481].…”
Section: Skin Tribologymentioning
confidence: 99%
“…The parameter δ is an important parameter for understanding the friction of viscoelastic materials. The parameter δ of the gel and elastic sponge exceeded that of the polymer film, which was hard to deform. …”
Section: Introductionmentioning
confidence: 99%
“…We also evaluated the friction dynamics on fractal agar gels, which mimic the shape and wettability of the tongue surface, and found that the friction profiles vary with the surface shape, vertical load, friction velocity and substance [15–18]. Asanuma et al found that the cosmetic sponge feels highly slippery when the friction force is low [19]. Kikegawa et al [20] reported that solid materials, such as powders and cloths, have a moist feel when the difference between the static and dynamic friction coefficients is large.…”
Section: Introductionmentioning
confidence: 99%